Climate actions by climate and non-climate researchers - Fabian Dablander; Maien S. M. Sachisthal; Jonas M. B. Haslbeck (npj Climate Action)
Abstract Tackling climate change requires both systemic changes and individual lifestyle changes. Are those best placed to understand the risks and solutions to climate change acting on their knowledge? In a large-scale study of N = 9220 researchers across 115 countries, we found that climate researchers reported engaging in considerably more advocacy and activism on climate change and, to a lesser extent, high-impact lifestyle changes than non-climate researchers.